One man's valor : Leo Baeck and the Holocaust : illustrated with photographs - Neimark, Anne E. (New York : E.P. Dutton, 1986)
Relates the story of a German Jew who became a great rabbi and natio nal spiritual leader and fought courageously against the persecution of his people during the Nazi years.
"Lodestar books."
Includes index.
Bibliography: p. 103.
Keywords: Baeck, Leo, -- 1873-1956 -- Juvenile literature; Baeck, Leo, -- 1873-1956. -- Juvenile literature; Theresienstadt (Concentration camp) -- Juvenile literature; Rabbis -- Germany -- Biography -- Juvenile literature; Holocaust, Jewish (1939-1945) -- Germany -- Juvenile literature; Rabbis. -- Juvenile literature. -- Germany; Holocaust, Jewish (1939-1945)